Profile of Hepatic Malondialdehyde (MDA) Levels in Peritonitis Model Rats After Administration with Garcinia tetrandra Pierre Methanol Extract: Profil Kadar Malondialdehyde (MDA) Hepar pada Tikus Model Peritonitis Setelah Pemberian dengan Ekstrak Metanol Garcinia tetrandra Pierre - Devyana Dyah Wulandari; Ary Andini; Suprapto Ma'at; Della Citra Ulan Sari (Medicra (Journal of Medical Laboratory Science/Technology), 2026)
Malondialdehyde (MDA) can reveal the oxidation processes occurring within cell membranes and is a reliable and accurate biomarker of oxidative stress. Increased levels of MDA are linked to pathological situations damage to blood vessel walls, heart disease, and cancer. Garcinia tetrandra Pierre, a Garcinia species that is rich in secondary metabolite compounds but has not been widely studied. This study aims to evaluate MDA levels in liver tissue homogenates of rats in a carrageenan-induced peritonitis model. This study began with a qualitative test of secondary metabolites to analyze the content of tannins, saponins, flavonoids, terpenoids and phenolics. In vivo tests using 30 male Wistar The rats were split up into six groups: the standard drugs group, the G. tetrandra methanolic extract treatment group dose of 200 mg/kg BW (P1), dose of 400 mg/kg BW (P2), and dose of 600 mg/kg BW (P3), the positive control group, and the negative control group. Liver tissue was made into homogenate to measure MDA levels using the UV-Vis spectrophotometer method. The results showed that the MDA levels in the liver of the treatment group were significantly different from the positive control group (P<0.05). This is supported by the presence of secondary metabolite compounds that are radical scavenging. It can be concluded that the methanol extract of G. tetrandra fruit skin is able to reduce liver MDA levels in peritonitis model mice so that it can be said to have the potential as a candidate for anti-inflammatory drugs.